Meaning-making in occupational therapy interventions: a scoping review/ A construção de sentidos nas intervenções em terapia ocupacional: uma revisão de escopo - de Mello, Ana Carolina Carreira; Araujo, Angélica da Silva; da Costa, Ana Lucia Borges; Marcolino, Taís Quevedo (Cadernos Brasileiros de Terapia Ocupacional, 2021)
Introduction: Meaning-making is an experience-centred process. It is an essential element for understanding the impact of occupational therapy interventions focused on fostering processes of becoming, one of the four integrated dimensions of meaningful occupation (along with doing, being, and belonging). Objective: This paper aims to explore further some of the aspects that are essential for meaning-making in occupational therapy interventions. Method: A scoping review guided by Arksey and O’Malley’s methodological framework was conducted. In the initial search, 528 articles were retrieved from three databases; 16 met the criteria for inclusion: articles in English, peer-reviewed, published between January 2008 and December 2017, that addressed some type of occupational therapy intervention, with data related to the meanings of the participants of the studies. Results: The articles address a multiplicity of populations, services, and fields of practice, in qualitative studies, with methodologies that prioritise reflection on the lived experience. Thematic analysis highlights the interconnection between being, doing, and belonging to foster meaning-making; implications of professional actions; and meaning-making triggered by reflective processes. Conclusion: Meaning-making demands reflection on the lived experience, and is influenced by human and physical environments. Both conditions/limitations and new skills/abilities enhance processes of meaning-making. Implications for future research are considered.